Tumor Growth Rate After Nadir Is Associated With Survival in Patients With EGFR-Mutant Non–Small-Cell Lung Cancer Treated With Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor. (2021) - Nishino, Mizuki; Lu, Junwei; Hino, Takuya; Vokes, Natalie I.; Jänne, Pasi A.; Hatabu, Hiroto; Johnson, Bruce E.
Abstract : PURPOSE: To investigate the association between tumor volume growth rate after the nadir and survival in patients with EGFR -mutant advanced non–small-cell lung cancer (NSCLC) treated with erlotinib. MATERIALS AND METHODS: Seventy-one patients with EGFR -mutant advanced NSCLC treated with erlotinib were studied for computed tomography tumor volume kinetics during therapy. The tumor growth rate after nadir was obtained using a previously published analytic module for longitudinal volume tracking to study its relationship with overall survival (OS). RESULTS: The median tumor volume for the cohort was 19, 842 mm 3 at baseline and 4, 083 mm 3 at nadir. The median time to nadir was 6.2 months. The tumor growth rate after nadir for loge V (the natural logarithm of tumor volume measured in mm 3 ) was 0.11/mo on average for the cohort (SE: 0.014), which was very similar to the previously validated reference value of 0.12/mo to define slow and fast tumor growth. The OS of 48 patients with slow tumor growth (⩽ 0.12/mo) was significantly longer compared with 23 patients with fast tumor growth (> 0.12/mo; median OS: 37.8 v 25.0 months; P = .0012). In Cox models, tumor growth rate was also associated with survival (regression coefficient: 3.9903; P = .0024; faster rate leads to increased hazards), after adjusting for time to nadir (regression coefficient: –0.0863; P = .0008; longer time to nadir leads to decreased hazards) and smoking history. CONCLUSION: In patients with EGFR -mutant advanced NSCLC treated with erlotinib, slower tumor growth rates after nadir were associated with longer OS, providing a rationale for using tumor growth rates to guide precision therapy for lung cancer.